ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DENGAN MODEL SKEMATIK FONG - Aurel Vania Karinda; Nicky Kurnia Tumalun; Derel Filandi Kaunang (Institut Pendidikan Tapanuli Selatan, 2023)
The purpose of this study was to find out the mistakes made by students in solving math word problems on equations and quadratic functions and their causal factors based on the Fong Schematic Model. The research was conducted at St. Catholic Middle School. Rosa de Lima Tondano for the 2021/2022 academic year. The research method used is descriptive qualitative research method. Data collection was carried out using tests and interviews. The research subjects were class IX students of St. Catholic Middle School. Rosa de Lima Tondano. The results of the research are based on the first level of the Fong Schematic Model, namely the E1 scheme has no completion, E2 uses irrelevant procedures, E3 the schematic is incomplete without errors, E4 the schematic is incomplete with errors, E5 the schema is complete with errors. The results of the research are based on the second level of the Fong Schematic Model, namely mathematical operations, mathematical themes and psychological factors. Factors causing the mistakes made by students are: 1) lack of understanding of how to solve problems, 2) lack of thoroughness in solving questions, 3) lack of understanding of how to factor quadratic equations, 4) rush in solving questions, 5) forgetting how to solve problems, 6) lack of skills in applying material to problems and 7) decreased student ability during the co-19 pandemic.